The causality between the consumer price index and macro economic policy variables in North African countries - Ibrahim, Rebahi; said, Mosbah (Journal of Ecohumanism, 2025)
This research paper examines the causal relationship between the Consumer Price Index (CPI) and macroeconomic policy variables in North African countries (Algeria, Tunisia, Egypt, and Morocco) during the period (2001-2020). The study employed a Panel Vector Error Correction Model (Panel VECM) to demonstrate this long-run and short-run causal relationship. The study concluded that there is at least one cointegration relationship, confirmed through (Pedroni, Kao, Johansen) tests, and stationarity of the variables at first difference. Furthermore, at least one causal relationship was identified. The rate of return to equilibrium, estimated at 3.5% annually, was also determined, which highlighted the weakness of the selected countries’ economies in correcting various incurred imbalances.